2018
DOI: 10.1101/507491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative interactions driveBotrytis cinereadisease outcome across the plant kingdom

Abstract: Host-pathogen interactions display a continuum of host ranges from extreme specialists limited to single hosts to broad generalists with hundreds of hosts. However, the existing models for host-pathogen dynamics are dominated by observations derived from specialist pathogens with qualitative virulence and tight host-pathogen co-evolution. It is not clear how appropriate the co-evolutionary model is in generalist pathogens that present quantitative virulence and broad host specificity. We infected 98 strains of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 83 publications
(90 reference statements)
1
15
0
1
Order By: Relevance
“…Surprisingly, the difference in aggressiveness between tomato ‐ and grapevine ‐ collected strains was observed when inoculating on bramble, whereas it belongs to a botanical family, the Rosaceae, distant from Solanaceae and Vitaceae. However, plant susceptibility to Botrytis cinerea shows very little association to the evolutionary distances between the plant species (Caseys et al ., ). Henceforth, theses aggressiveness variations could be linked to species‐specific interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Surprisingly, the difference in aggressiveness between tomato ‐ and grapevine ‐ collected strains was observed when inoculating on bramble, whereas it belongs to a botanical family, the Rosaceae, distant from Solanaceae and Vitaceae. However, plant susceptibility to Botrytis cinerea shows very little association to the evolutionary distances between the plant species (Caseys et al ., ). Henceforth, theses aggressiveness variations could be linked to species‐specific interactions.…”
Section: Discussionmentioning
confidence: 97%
“…One noticeable exception is the population of B. cinerea collected from various hosts in California (Ma & Michailides 2005), for which whole-genome sequencing data and cross-infectivity assays revealed small differences in pathogenicity against different hosts and shallow population structure (Atwell et al . 2015; Caseys et al . 2020; Soltis et al .…”
Section: Discussionmentioning
confidence: 99%
“…in Chile, Tunisia, Hungary, United Kingdom; Walker 2016). One noticeable case is the population of B. cinerea collected from various hosts in California (Ma & Michailides 2005), for which whole-genome sequencing data did not detect any host-associated population structure despite differences in pathogenicity against different hosts (including tomato) in cross-infectivity assays (Atwell et al 2015; Caseys et al 2020; Soltis et al 2019). In France, previous research concluded that B. cinerea populations were differentiated according to some of their hosts, including tomato, grapevine and, to a lesser extent, bramble (Fournier & Giraud 2008; Walker et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a global set of populations of the major wheat pathogen Z. tritici , a large set of loci associated with pathogen virulence and reproduction on different hosts were identified [38] , [162] . A large infection matrix of 98 strains of Botrytis cinerea and 90 plant genotypes of eight species revealed a highly polygenic architecture of pathogen virulence and host specialization [163] . Hence, simultaneously extending genetic diversity screens of the host and pathogen provides a powerful approach to comprehensively map the genetic architecture of virulence and resistance.…”
Section: Introductionmentioning
confidence: 99%